Assessment of patch test results carried out during ten years in a city in southern Brazil - Mariane Corrêa-Fissmer; Cintia Camila Dalazen; Bárbara Piacentini Ferreira; Betine Pinto Moehlecke Iser (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Contact dermatitis affects up to 20% of the population. Patch testing for contact allergy may be needed to confirm the diagnosis. Objectives: To describe and discuss the results of patch tests performed in a city in southern Brazil. Methods: A cross-sectional analysis was performed on all skin test results over ten years. Variables such as gender, age at the time of testing, and test results were evaluated. Triggering factors, duration of complain, and previous medications used related to the clinical history were retrieved for some patients by reviewing their medical records. Results: The sample was composed of 539 patch tests, of which 411 (76.2%) were from women. The age of the tested subjects ranged from 5 to 87 years. The prevalence of positive reactions in the patch tests was 391 (72.5%). The most prevalent positive reaction was to nickel sulfate (196; 36.4%), which had statistical significance when associated with female gender (p<0,001). Study limitations: Database obtained through secondary sources (the reports of the exams and the medical records), occurring the incomplete registration of some information. Conclusions: Data analysis at the local level is important to define preventive policies.